022 Dynamic three-dimensional whole heart magnetic resonance myocardial perfusion imaging: validation against pressure wire derived fractional flow reserve for the detection of flow-limiting coronary heart disease. (16th May 2012) - Jogiya, R; Morton, G; De Silva, K; Perera, D; Redwood, S; Kozerke, S; Nagel, E; Plein, S
Abstract : Background: Three-dimensional (3D) myocardial perfusion cardiovascular magnetic resonance (CMR) has recently been proposed to overcome the limited spatial coverage of conventional perfusion CMR methods. The method has shown good diagnostic accuracy for the detection of coronary artery disease determined by quantitative coronary angiography. However the relationship between the severity of a coronary stenosis on quantitative coronary angiography and its functional significance is variable. Pressure wire-derived fractional flow reserve (FFR) <0.75 correlates closely with objective evidence of reversible ischaemia and it has been demonstrated that ischaemia-guided PCI confers a prognostic benefit. Objectives: To determine the diagnostic accuracy of whole heart 3D myocardial perfusion CMR against invasively determined FFR. Methods: 55 patients referred for angiography underwent rest and adenosine stress 3D myocardial perfusion CMR at 3Tesla (3D turbo gradient echo, flip angle 15, TR 2.0 ms/TE 1.0 ms, 12 slices of 5 mm thickness, in-plane resolution 2.3×2.3 mm 2, 10-fold k-space and time k-t broad linear speed up technique acceleration with k-t principal component analysis). Perfusion was scored visually as on a coronary territory basis on a score from 0 to 3. Ischaemic burden was calculated by quantitative segmentation of the volume of hypoenhancement. The FFR was measured in vessels with >50% severity stenosis. Fractional flow reserve <0.75 was considered haemodynamically significant. Results: Two patients were excluded (one due to claustrophobia, the other had poor image quality). From the remaining 53 patients and 159 coronary vessels, 64 underwent pressure wire assessment and 39 had an FFR<0.75. Sensitivity, specificity and diagnostic accuracy of CMR analysis per patient was 90%, 91% and 91%, respectively for the detection of significant coronary artery disease. By coronary territory the values were 79%, 92% and 88%. Conclusion: 3D CMR stress perfusion can detect functionally significant coronary artery disease with excellent sensitivity, specificity and predictive values when compared with FFR. 3D CMR perfusion imaging may offer an alternative method of detecting ischaemia for the purpose of guiding revascularisation and risk stratification.